Challenges and Prospects for Organic Farming: A Case Study from India - Kaur, Harmandeep (Gyan Management Journal, 2023)
Several past studies have considered organic farming as it serves as a  responsive sustainable approach to the rural development. This study  emphasises and focuses on the opportunities and constraints in organic  farming in context of India. There are several cost and marketing related  problems specific to organic food. This study identify the following areas  to addresss these problems in the country: develop a regional programme  to address specific regional problems, take into account the unique  conditions prevailing in the region; provide financial assistance for the  effective implementation of organic projects and programmes, access to  advanced technology, effective information sharing platforms. The organic  movement’s capacity for adaptation and learning from past experiences  will determine if organic farming is able to fully realise its capacity for  fostering resilience( Milestad and Darnhofer, 2003).
Keywords: Challenges; Prospects; A Case Study